House of sand and fog - Dubus, Andre, 1959- (New York : Vintage Contemporaries, 2000)
On a road crew in California, a former colonel in the Iranian Air Force under the Shah yearns to restore his family's dignity. When an attractive bungalow comes available on county auction for a fraction of its value, he sees a great opportunity for himself, his wife, and his children. But the house's former owner, a recovering alcoholic and addict down on her luck, doesn't see it that way, nor does her lover, a married cop driven to extremes to win her love and get her house back.
Accelerated Reader AR
Reading Counts RC
National Book Award Finalist, 1999.
Keywords: Iranian Americans -- Fiction; Home ownership -- Fiction; Immigrants -- Fiction; Home ownership; Immigrants; Iranian Americans; San Mateo County (Calif.) -- Fiction; California -- San Mateo County; Domestic fiction; Miscellaneous fiction; Domestic fiction; Fiction; Domestic fiction